If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -6m = -104 Solving 10 + -6m = -104 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -6m = -104 + -10 Combine like terms: 10 + -10 = 0 0 + -6m = -104 + -10 -6m = -104 + -10 Combine like terms: -104 + -10 = -114 -6m = -114 Divide each side by '-6'. m = 19 Simplifying m = 19
| 2x^2+7x-2=x^2+2x | | 4x^2-xy-3y^2= | | -10=10k-90 | | q+2=5 | | -103=-9x-13 | | x^2+8x+68=0 | | 9(9x+4)= | | x+(x+4)=2(x-3x) | | 10x^2-5x-5= | | 8-x+1=6 | | x+3x=2(x-4) | | 4y^2+20Y=0 | | 3(7x-5)= | | x+4=2(x-3x) | | p^2+5p=6 | | 2b^2=9b+5 | | 5(6+x)=85 | | x^2=4-7x | | 3(x^2-x)-4(x^2+x)=-3(x+1)-4(x+2) | | 3r^3+18r^2=21r | | 5x=32 | | 75y^2-147=0 | | 2x^2+9x=8 | | X^2-21x+54=0 | | 3x+6=-21 | | Z^2-21z+54=0 | | A^2-25a=0 | | 3x^2-42x-216=0 | | x+4y=20 | | 3x-14x=-11 | | 6+x=5x-18 | | 1x=x-3x+2(x+4) |